PROFESIONALISME AKUNTAN SEBAGAI KOMPONEN PENDUKUNG PERTAHANAN NEGARA DALAM MEMBANGUN NEGERI - Tien Norma Habsari; Zainal Abidin Sahabuddin; Sri Sundari (Program Studi Akuntansi, 2022)
This study aims to analyze the professionalism of accountants as a component of supporting national defense. Supporting components that can increase the strength and capability of the main components and reserve components in the face of military and non-military threats. This study uses a qualitative approach with descriptive analysis method through collecting data from several books, journals, printed or electronic documents, and other sources of data or information. The research is intended to analyze the data by using data reduction techniques. The results of this study require selfdevelopment, improvement of soft skills, building networks with entrepreneurs, the government, and even accounting students with KAP and business organizations also need to be developed in order to increase the number of professional accountants in Indonesia. So that it is hoped that Indonesian Accountants as a supporting component can make a maximum contribution in building a prosperous country.